ADIPONEKTIN MEREGULASI TURUN EKSPRESI iNOS PADA KULTUR HUVEC’s YANG DIPAPAR LIPO POLYSACCHARIDE (LPS) - Hernani, Yully Endang (Fakultas Kedokteran Universitas Brawijaya, 2008)
ABSTRACT Adiponectin is a adipocyte derivate protein involves in sensitivity of insulin, anti-inflamation, and anti-atherogenic found largely in plasma. The decrease of adiponectin in the plasma is related to obesity, cardiovascular diseases, type II diabetes, hypertension and vascular injuries in nice. In vivo research on strain balb/c mice showed that excessive Adiponectin expression inhibits atherosclerosis with Apo E deficiency. The aim of this research is to find protective mechanisms of adiponectin on vascular utilizing in-vitro Infected HUVEC’s culture. There were 5 groups :(A) control negative group or normal HUVEC’s,